, Setkom tysięcy, co imion nie mają na grobie... ” szadkowicki cmentarz wojenny z okresu bitwy łódzkiej (1914) - Młyńska, Alicja (Biuletyn Szadkowski, 2013)
Almost 200 places of burial of soldiers of both annies fighting in the First World War have survived in the region of Łódż. They include cemeteries and cemetery Sections where soldiers fighting in the so-called battle of Łódż, which took place in 1914, found their last resting place. One of these cemeteries is in Szadkowice, and even though it does not really stand out from other resting places of the battle of Łódż soldiers, it deserves our attention. The cemetery in Szadkowice located on the edge of the forest survived the interwar period, when many mass graves were łiquidated and bodies exhumed to nearby cemeteries. The original number of 21 buried bodies grew then to nearły 180, and the cemetery became a mass grave of Germans, Russians and Austro-Hungarians and kind of lapidarium.